Of sinners and saints - Soriquez, Ruben Maria, 1971-; Ramos, Alejandro Mirasol; Bagatsing, Raymond; See Thru Pictures (Firm); Leomark Studios ([Quezon City, Philippines] : See Thru Pictures, 2014)
Leonardo is an Italian missionary who counsels battered women and teach poor children in the Philippines. But problems arise when he meets Merlinda, a young woman with a violent husband and a 6 year old missing child. --
Originally released as a motion picture in 2015.
Ruben Maria Soriquez, Raymond Bagatsing, Polo Ravales, Chanel Latorre, Richard Quan, Althea Vega, Sue Prado, Nicoli Lista, Jay Jay Junio.
Cinematographer, Apollo Anao ; editor, Ruben Maria Soriquez ; music, Franco Eco.
In English and Tagalog; English subtitles for Tagalog dialogues; closed captioning available.
Winner of the Award of Feature Film, at the Accolade Competition 2015.
Winner of the Award Best Use of Film for Social Change, at the Accolade Competition 2015.
Keywords: Priests -- Fiction; Missionaries -- Fiction; Man-woman relationships -- Fiction; Church work with children -- Fiction; Church work with women -- Fiction; Infanticide -- Fiction; Payatas (Philippines) -- Religious life and customs; Action and adventure films; Thrillers (Motion pictures); Feature films; Internet videos; Streaming video